CARDIOVASCULAR AUTONOMIC NEUROPATHY: A RISK FACTOR FOR THE PROGRESSION OF COMPLICATIONS OF DIABETES MELLITUS - Bobojonova Shohista Davronbekovna; Turdiyeva Muyassar Ernazarovna; Xudayberganova Shaxnoza Baxtiyorovna; Majidova Odila Zaripovna; Usmonova Xilola Sayfullayeva (Western European Studies, 2024)
Cardiovascular autonomic neuropathy (CAN) is a severe and underdiagnosed complication of diabetes mellitus, significantly increasing the risk of cardiovascular morbidity and mortality. CAN results from damage to the autonomic nerves that control heart rate and vascular function, leading to an array of symptoms, including resting tachycardia, orthostatic hypotension, and silent myocardial ischemia. This article explores the pathophysiological mechanisms underlying CAN, its clinical manifestations, diagnostic approaches, and the link between CAN and the progression of other diabetes-related complications. Furthermore, it highlights preventive and therapeutic strategies aimed at early detection and management of CAN, emphasizing its role in reducing the overall burden of diabetes complications
Keywords: Cardiovascular autonomic neuropathy; diabetes mellitus; complications